On teaching phraseology during classes of Russian as a foreign language - Madina N. Mukova, Emma L. Kokova, Valentina S. Sabanchieva,; Natalya N. Malahova, Zalina O. Dotkulova, Elena I. Gorbulinskaya, (Opción, 2019)
This article is aimed at identifying how to accurately understand and interpret idioms and phraseological units as well as properly use them in speech. The main method to investigate this issue is to compare Russian phraseological units with their equivalents in the native language of a foreign student. As a result, teaching a foreign language in a multicultural society facilitates and extends the horizons of the learner’s opportunities, allowing him to join the world’s values, feel more freedom. In conclusion, the study of phraseology should be conducted gradually, while students acquire lexical and grammatical material.